Wavelength multiplexing encryption using joint transform correlator architecture - Amaya Robayo, Dafne Cecilia (2009)
We show that multiple secure data recording under a wavelength multiplexing technique is possible in a joint transform correlator (JTC) arrangement. We evaluate both the performance of the decrypting procedure and the influence of the input image size when decrypting with a wavelength different from that employed in the encryption step. This analysis reveals that the wavelength is a valid parameter to conduct image multiplexing encoding with the JTC architecture. In addition, we study the influence of the minimum wavelength change that prevents decoding cross talk. Computer simulations confirm the performance of the proposed technique.